Dependence of wet etch rate on deposition, annealing conditions and etchants for PECVD silicon nitride film - 唐龙娟 朱银芳 杨晋玲 李艳 周威 解婧 刘云飞 杨富华 (Journal of semiconductors, 2009)
The influence of deposition, annealing conditions, and etchants on the wet etch rate of plasma enhanced chemical vapor deposition （PECVD） silicon nitride thin film is studied. The deposition source gas flow rate and annealing temperature were varied to decrease the etch rate of SiNx：H by HF solution. A low etch rate was achieved by increasing the SiH4 gas flow rate or annealing temperature, or decreasing the NH3 and N2 gas flow rate. Concentrated, buffered, and dilute hydrofluoric acid were utilized as etchants for Sit2 and SiNx：H. A high etching selectivity of Sit2 over SiNx：H was obtained using highly concentrated buffered HE